Evaluasi tahapan akuntansi belanja pemeliharaan gedung pada Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten Minahasa Selatan - Sumampouw, Hesky Jeremy; Tinangon, Jantje J.; Mawikere, Lidia M (Yayasan Widyantara Nawasena Raharja, 2024)
It is important to allocate adequate maintenance spending to maintain the condition of government assets so that they continue to function well. Every year the budget allocation has become commonplace for every SKPD. However, sometimes the allocated budget results in excess funds and is not maximized with other priority spending. The aim of this research is to determine the stages of accounting for building maintenance expenditures at the South Minahasa Regency Regional Financial and Asset Management Agency. The type of research used in this research is qualitative. The data collection methods used were interviews and documentation studies. This research was carried out at the South Minahasa Regency Regional Financial and Asset Management Agency. The results of this research show that the South Minahasa Regency Regional Financial and Asset Management Agency carries out the accounting stages for building maintenance expenditure based on Permendagri 77 of 2020.